Analisis Respon Peserta Didik terhadap Penerapan Pendekatan Discovery Learning pada Materi Laju Reaksi Kelas XI IPA SMA Kristen Maktihan Malaka (HISKIA : Jurnal Ilmu Kimia & Pendidikan Kimia, 2025)
Learner response is the interaction and response given by students to learning. Discovery Learning is an approach that encourages students to discover concepts for themselves through exploration and observation. The response of students in class XI IPA SMA Kristen Maktihan Malaka to chemistry learning is still low. This study aims to analyse the response of students in class XI IPA to the Discovery Learning approach on reaction rate material. The sample in this study were students of class XI IPA SMA Kristen Maktihan. The type of research used in this research is descriptive quantitative. The instrument used is a questionnaire sheet of students' responses. This study used a questionnaire technique in data collection. The results of this study indicate that the response of students in class XI IPA SMA Kristen Maktihan Malaka to the Discovery Learning approach on reaction rate material is very good with an average percentage obtained of 91%.